Pa’garasik di Campalagian: Kajian Pelayaran dan Perdagangan, 1950-1970 - Nurul Rahma; Ahmadin Ahmadin; Najamuddin Najamuddin (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
This study examines the practice of pa’garasik in Campalagian, Polewali Mandar Regency, during the 1950s–1970s as a form of traditional maritime trade and navigation among the Mandar people. The background of this research lies in the need to reconstruct local maritime economic history that was built on trust and to explore the cultural values embedded within it. The objectives are to describe the origins of pa’garasik, analyze its sailing patterns and traded commodities, and explain its socio-economic impacts as well as cultural relevance. The study employs a historical method with a qualitative approach through four stages: heuristics, source criticism, interpretation, and historiography. Primary data were collected through interviews with community elders and families of former pa’garasik practitioners, along with observations of historical sites. Secondary data were obtained from literature, archives, and previous studies related to Mandar maritime culture. Findings reveal that pa’garasik functioned as a trust-based consignment trade system, where goods were entrusted to sailors without written contracts. Its sustainability relied on values such as amanah (trustworthiness), siri’ na pacce (honor and empathy), honesty, and social solidarity. At its peak, pa’garasik connected Campalagian with regions such as Kalimantan, Nusa Tenggara, and even the Malay Peninsula, playing a crucial role in goods distribution, improving local livelihoods, and expanding social-cultural networks. However, by the late 1970s, this practice declined due to the modernization of sea transport, centralized development policies, and shifting aspirations of younger generations. Despite its decline, the cultural values of pa’garasik remain relevant today as an inspiration for community-based economic models, local history education, and maritime cultural tourism. Thus, pa’garasik should be preserved as an intangible cultural heritage that strengthens Mandar identity and enriches Indonesia’s maritime legacy.